Linear and whorled nevoid hypermelanosis: A rare familial case report (Indian Journal of Case Reports, 2019)
Linear and whorled nevoid hypermelanosis (LWNH), also known as ‘zebra-like pigmentation’ is characterized by linear and swirling streaks of hyperpigmentation along the Blaschko’slines without preceding inflammation and atrophy. It is mainly located on trunk and limbs. The hyperpigmentation may be present at birth or may develop by early childhood. Very rarely, familial cases have been described. Here, we are reporting one such rare case of familial LWNH in a 19-year-old female.